Design of water Ambulance for Improving Healthcare Services in Mahakam Ulu Regency - Sitorus, Chris Jeremy Verian; Muhammad Uswah Pawara; Hidayat, Rahmat; Hariyono; Harlian Kustiwansa; Alamsyah; Suardi; Muhammad Anjas Syam; Jusma Wahidah; Cindy Lionita Agusty (International Journal of Marine Engineering Innovation and Research, 2025)
Mahakam Ulu Regency's landscape is dominated by tropical rainforest, with transportation access heavily reliant on river routes. The region is home to 245 rivers, ten of which are classified as major rivers and are distributed across all sub-districts. The Mahakam River serves as the main artery for community activities, including the emergency transport of patients. Nevertheless, serious challenges persist due to limited healthcare infrastructure and inadequate medical transport, which hinder the timely treatment of patients. Currently, there are no water ambulances specifically designed for emergency medical services, leading to delays and increased risks of patient morbidity and mortality.The aim of this study is to develop a water ambulance vessel designed to serve as a dedicated river based medical transport in Mahakam Ulu. A parent ship design approach was applied in the development process. The principal dimensions defined in this study are as follows:Length Overall (LOA): 10.5 m,Beam (B): 3.15 m, Depth (H): 1.35 m, Draft (T): 0.65 m, Service Speed (Vs): 20 knots, Accommodation: 10 crew and passengers. Keywords- Mahakam Ulu, Mahakam River, Water Ambulance, Parent Ship Design